Pengaruh Perceived Usefulness, Perceived Enjoyment dan Kepercayaan Terhadap Continuance Intention Melalui Kepuasan Pada Generasi Millenial Pengguna E-Wallet di Kota Medan - Mutiara Anasta Ayu Damanik; Amrin Fauzi; Syafrizal Helmi Situmorang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aimed to analyze the effect of perceived usefulness, perceived enjoyment, trust through satisfaction on continuance intention. This type of research is an associative study and the population in this study is an unknown number of e-wallet users. The sample criteria used in this study are the Millennial generation in Medan City who are e-wallet users. Considering the population is not known with certainty, the number of samples is 140 respondents. The sampling method used is convenience sampling. Data analysis was carried out through PLS-SEM using the SmartPLS program. The results showed that directly perceived usefulness, perceived enjoyment, trust, and satisfaction had a positive and significant effect on continuance intention, and indirectly perceived benefits, perceived enjoyment, and trust had a positive and significant impact on continuing intentions through satisfaction.